A finite element-based optimization of composite wrap repair for welded pipelines with Surface Cracks: influence of geometry, adhesive properties, and internal pressure on mode I fracture behavior - Nedir, Hachemi; Mahmoudi, Noureddine; Khelil, Foudil; Bouadi, Abed; Moulai Arbi, Youcef (Vojnotehnički glasnik / Military Technical Courier, 2026)
Introduction/purpose: The structural integrity of pressurized pipelines is often threatened by surface cracks, especially in welded regions. This study evaluates the effectiveness of composite wrap reinforcement in repairing longitudinal semi-elliptical cracks in welded steel pipelines subjected to internal pressure. Although environmental effects such as temperature, moisture, and chemical exposure were not modeled, they are acknowledged as key factors influencing the long-term durability of composite repairs.Methods: A three-dimensional finite element model was developed for a welded pipeline (outer diameter = 1016 mm, thickness = 12.8 mm) containing an external semi-elliptical crack (2c = 10.24 mm, a = 2.56 mm). The Virtual Crack Closure Technique (VCCT) was applied to compute Mode I Stress Intensity Factors (SIFs) under internal pressures of 2–12 MPa. A parametric study assessed the influence of patch length (100–400 mm), thickness (6–12 mm), and circumferential coverage angle (30°–360°), as well as adhesive shear modulus, thickness, and debonding effects.Results: Increasing patch length, thickness, and coverage angle reduced SIFs, improving crack-tip stress attenuation. A higher adhesive shear modulus enhanced interfacial load transfer, while excessive adhesive thickness impaired efficiency. Localized adhesive debonding significantly increased SIFs under pressure, highlighting the sensitivity of repair performance to bonding quality.Conclusions: This study provides design insights for optimizing composite reinforcement in welded pipeline repairs. Although a rectangular patch was analyzed, future work should investigate alternative geometries to mitigate edge stress concentrations and incorporate fatigue and environmental effects to better predict long-term service performance.
Keywords: pipeline weld repair; composite wrap reinforcement; stress intensity factor (SIF); crack propagation; finite element method (FEM)